Reward eliminates retrieval-induced forgetting - Imai, Hisato; Kim, Dongho; Sasaki, Yuka; Watanabe, Takeo (Proceedings of the National Academy of Sciences - PNAS, 2014)
Although it is well known that reward enhances learning and memory, how extensively such enhancement occurs remains unclear. To address this question, we examined how reward influences retrieval-induced forgetting (RIF) in which the retrieval of a nonpracticed item under the same category as a practiced item is worse than the retrieval of a nonpracticed item outside the category. Subjects were asked to try to encode category-exemplar pairs (e.g., FISH–salmon). Then, they were presented with a category name and a two-letter word stem (e.g., FISH–sa) and were asked to complete an encoded word (retrieval practice). For a correct response, apple juice was given as a reward in the reward condition and a beeping sound was presented in the no-reward condition. Finally, subjects were asked to report whether each exemplar had been presented in the first phase. RIF was replicated in the no-reward condition. However, in the reward condition, RIF was eliminated. These results suggest that reward enhances processing of retrieval of unpracticed members by mechanisms such as spreading activation within the same category, irrespective of whether items were practiced or not. Significance Although it is well known that reward enhances learning and memory, how extensively such enhancement occurs remains unclear. We examined how reward influences retrieval-induced forgetting (RIF) in which the retrieval of a nonpracticed item under the same category as a practiced item is worse than the retrieval of a nonpracticed item outside the category. RIF was abolished if a juice reward was given for correct answers in the practice phase. These results suggest that reward enhances processing of retrieval of unpracticed members by mechanisms such as spreading activation within the same category, irrespective of whether items were practiced or not.